Adolescent Energy Drink Consumption and Academic Risk: Results From the Monitoring the Future Study, 2010–2016. (April 2022) - Leal, Wanda E.; Jackson, Dylan B.; Boccio, Cashen M.
Aims: The current study aims to examine the role of energy drink and energy shot consumption in school disengagement, low academic performance, and academic expectations, and investigates the robustness of these associations across sex, grade, race, and substance use history. Method: This study employs a pooled cross-sectional design and uses a nationally representative sample of 8th (ages 13–14 years) and 10th (ages 15–16 years) grade adolescents from seven recent cohorts (2010–2016) of the Monitoring the Future study. Logistic regression and negative binomial regression were employed to examine the association between energy drink and energy shot consumption and academic risk factors, controlling for sociodemographic factors and other health and social behaviors. Ancillary robustness checks across key subgroups in the data were also performed. Results: The results indicate that energy drink and energy shot consumers are significantly more likely to report all academic risk outcomes. Specifically, youth who heavily use energy drinks and shots have significantly higher odds of each of the academic risk outcomes relative to both less habitual users and nonusers. These patterns hold across subgroups, despite associations being somewhat stronger among females, younger participants, Whites, and youth with no substance use history. Conclusions: The current study suggests that energy drink consumption (particularly heavy consumption) may be an early warning sign of academic risk. It may be beneficial to limit adolescent energy drink consumption, provide early intervention for heavy adolescent consumers, and raise awareness of the dangers associated with their use.